Gender differences in the mental symptom network of high school students in Shanghai, China: a network analysis - Zheng Zhang; Andi Qiu; Xiangyan Zhang; Yixin Zhao; Lu Yuan; Jing Yi; Qi Zhang; Haidong Liu; Ruoheng Lin; Xiangbin Zhang (BMC, 2024)
Abstract Background Adolescence is a critical period for the onset of mental health issues. In China, high school students face significant academic and social pressures, leading to high rates of mental health challenges. Gender differences in the manifestation of these symptoms have been observed, with boys and girls exhibiting distinct psychological profiles. Objective This study aims to explore the structure of psychological symptoms among Chinese high school students using network analysis, focusing on identifying core symptoms and gender differences in symptom networks. The key objectives are to: 1) identify the central psychological symptoms for boys and girls, and 2) uncover the interactions between symptoms to inform targeted interventions. Methods A cluster sampling method was used to recruit 3,769 high school students (2,206 males and 1,563 females) in Shanghai. The Middle School Students Mental Health Scale (MSSMHS) was administered, and network analysis was conducted using the R packages bootnet and qgraph to assess symptom network edges, centrality, and network strength. Comparisons between male and female networks were made. Results Network analysis showed tightly connected symptom networks for both genders, with 43 non-zero edges for boys (sparsity 0.04) and 39 for girls (sparsity 0.13). Depression was the core symptom for boys (centrality 1.20), while anxiety was central for girls (centrality 1.46). Boys showed a stronger link between interpersonal sensitivity and depression (edge value 0.20), while girls exhibited a stronger connection between anxiety and obsessive-compulsive symptoms (edge value 0.16). Network comparison tests revealed no significant differences in overall network strength between boys (4.625) and girls (4.660), with P-values greater than 0.05 across all comparisons. Conclusion This study highlights significant gender differences in the psychological symptom networks of Chinese high school students. Depression and anxiety emerged as core symptoms for boys and girls, respectively. These findings provide a foundation for developing gender-sensitive mental health interventions, emphasizing the need for tailored approaches based on gender-specific symptom profiles.